Network stability in organizational flux: the case of in-house management consulting - Panitz, Robert; Glückler, Johannes (Social networks, 2020)
This article explores the effects of organizational flux on the statics of interpersonal knowledge exchange structures. In our empirical case, organizational flux refers to high rates of personnel turnover, temporary project work, constant recombination of team memberships, and short-term collaboration. Network statics refers to the balance between forces composing and decomposing a network. Set in continuously changing organizational compositions of an in-house management-consulting unit, our study offers insights into the relationship between organizational characteristics and informal networks between experts. Against conventional intuition, we find a dense and stable structure of knowledge exchange. Furthermore, we elaborate on the two concepts of organizational flux and network statics, by comparing the observed structures with theoretical (random graphs) and empirical references (other empirical cases), and by using ERG models to account for different factors of organization, social balance, and individual attributes.
Gesehen am 25.03.2020